Divergent Associations of Antecedent- and Response-Focused Emotion Regulation Strategies with Midlife Cardiovascular Disease Risk. Issue 2 (26th February 2014) - Appleton, Allison A.; Loucks, Eric B.; Buka, Stephen L.; Kubzansky, Laura D.
Abstract: Background: It is not known whether various forms of emotion regulation are differentially related to cardiovascular disease risk. Purpose: The purpose of this study is to assess whether antecedent and response-focused emotion regulation would have divergent associations with likelihood of developing cardiovascular disease. Methods: Two emotion regulation strategies were examined: reappraisal (antecedent-focused) and suppression (response-focused). Cardiovascular disease risk was assessed with a validated Framingham algorithm that estimates the likelihood of developing CVD in 10 years. Associations were assessed among 373 adults via multiple linear regression. Pathways and gender-specific associations were also considered. Results: One standard deviation increases in reappraisal and suppression were associated with 5.9 % lower and 10.0 % higher 10-year cardiovascular disease risk, respectively, in adjusted analyses. Conclusions: Divergent associations of antecedent and response-focused emotion regulation with cardiovascular disease risk were observed. Effective emotion regulation may promote cardiovascular health.